IMPROVING THE PROCEDURE FOR USING EXPERT WORK IN AUDITING - Ochilov Farxodjon Shavkatjon ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In this article, how to use expert work in auditing and improve its procedure, in what cases an expert is needed for an auditor and what types of expert opinion are divided, information about what processes exist in each type, and on increasing the role of an expert in auditing. suggestions and recommendations were given.